Genome-wide analyses reveals a glucosyltransferase involved in rutin and emodin glucoside biosynthesis in tartary buckwheat. (15th July 2020) - Yin, Qinggang; Han, Xiaoyan; Han, Zongxian; Chen, Qingfu; Shi, Yuhua; Gao, Han; Zhang, Tianyuan; Dong, Gangqiang; Xiong, Chao; Song, Chi; Sun, Wei; Chen, Shilin
Highlights: Temporal and spatial transcripts of 106 FtUGTs were analyzed in genome level. FtUGT73BE5 was identified dominating the first step of rutin glycosylation. FtUGT73BE5 was demonstrated to catalyze emodin to form emodin 6- O -glucoside . MeJA up-regulates transcript of FtUGT73BE5 ; it was related to anti-adversity. Abstract: With people's increasing needs for health concern, rutin and emodin in tartary buckwheat have attracted much attention for their antioxidant, anti-diabetic and reducing weight function. However, the biosynthesis of rutin and emodin in tartary buckwheat is still unclear; especially their later glycosylation contributing to make them more stable and soluble is uncovered. Based on tartary buckwheat' genome, the gene structures of 106 UGTs were analyzed; 21 candidate FtUGTs were selected to enzymatic test by comparing their transcript patterns. Among them, FtUGT73BE5 and other 4 FtUGTs were identified to glucosylate flavonol or emodin in vitro ; especially rFtUGT73BE5 could catalyze the glucosylation of all tested flavonoids and emodin. Furthermore, the identical in vivo functions of FtUGT73BE5 were demonstrated in tartary buckwheat hairy roots. The transcript profile of FtUGT73BE5 was consistent with the accumulation trend of rutin in plant; this gene may relate to anti-adversity for its transcripts were up-regulated by MeJA, and repressed by ABA.